Default Effects of Credit Card Minimum Payments. (August 2022) - Sakaguchi, Hiroaki; Stewart, Neil; Gathergood, John; Adams, Paul; Guttman-Kenney, Benedict; Hayes, Lucy; Hunt, Stefan
Credit card minimum payments are designed to ensure that individuals pay down their debt over time, and scheduling minimum automatic repayments helps people avoid forgetting to repay. Yet minimum payments have additional, unintended psychological default effects by drawing attention away from the card balance due. First, once individuals set the minimum automatic repayment as the default, they then neglect to make the occasional larger repayments they made previously. As a result, individuals incur considerably more credit card interest than late payment fees avoided. Using detailed transaction data, the authors show that approximately 8% of all of the interest ever paid is due to this effect. Second, manual credit card payments are lower when individuals are prompted with minimum payment information. In an experiment, the authors test two new interventions to mitigate this effect—a prompt for full repayment and a prompt asking those repaying little to pay more—yielding large counter effects. Thus, shrouding the minimum payment option for automatic and manual payments and directing attention to the full balance may remedy the unintended effects of default minimum payments.